Namibia : 2019 Article IV Consultation-Press Release and Staff Report. (IMF Staff Country Reports; Country Report ;, 2019)
This 2019 Article IV Consultation with Namibia discusses that with the temporary stimuli now ended, the economy is rebalancing while the government is implementing a significant fiscal consolidation. A likely slow recovery, the need for further fiscal adjustment to bring public debt to a sustainable path, persistent inequalities and structural impediments to growth, point to a challenging outlook. Immediate measures are needed to deliver the authorities' fiscal adjustment plans and bring public debt to a sustainable path. Policies should combine spending reductions and revenue increases that support long-term growth. Better targeting of cash transfers would protect the poor. Structural reforms are urgently needed to strengthen productivity and external competitiveness and boost long-term growth. Reforms should streamline business regulations, contain public sector wage dynamics, and reduce costs of key production inputs. Over time, it is important to remove non-tariff barriers to exports, foster the adoption of new technologies, and address shortages of skilled workers.